Pengaruh Faktor Kualitas Sumber Daya Manusia Terhadap Kinerja Pegawai Pada Balai Latihan Transmigrasi di Makassar - Andi Bintang Balele; Mardiana Ibrahim (Transformasi: Journal of Economics and Business Management, 2022)
The aim of the research is to determine the quality factors of human resources that influence employee performance at the Transmigration Training Center in Makassar. To find out the factors that have a dominant influence on employee performance at the Transmigration Training Center in Makassar. This research uses quantitative research methods. Research results: The influential variables are education (X1), skills (X2), length of service (X3) and work discipline (X4) which together have a significant influence on the performance of employees at the Transmigration Training Center in Makassar. This can be seen by the F table value being greater than F Calculation or a significance of 0.000 which is smaller than 0.05. Of all these influencing factors, it turns out that the skill variable (factor) (X2) is dominant in increasing the performance of employees at the Transmigration Training Center in Makassar. This can be seen in the regression coefficient value (0.313 which is greater than the regression coefficient value of other independent variables) and the significance value (0.000).